Variación de la composición química de los aceites esenciales de cúrcuma (Curcuma longa), hierba luisa (Cymbopogon citratus) y jengibre (Zingiber officinale) en función del tipo de suelo y las variables climáticas de la zona de cultivo de las especies vegetales en las provincias de Santa Elena, Guayas, Los Ríos, Bolívar, Cotopaxi, Tungurahua, Chimborazo, Morona Santiago y Pastaza. - Altamirano Campaña, Fredy Eduardo (2016)
This research analyze the variation of the chemical composition of essential oils: Turmeric (Curcuma longa), Lemongrass (Cymbopogon citratus) and Ginger (Zingiber officinale) according to soil type and climatic variables in the area of culture plant species in Coast, Sierra and Eastern regions of the central sector of Ecuador; methods of chemical and physical analysis was used to determine the type of soil, pH, conductivity, moisture, organic matter and nutrients (K, Fe, N, P); essential oils were extracted by the technique of steam and the chromatographic profiles were obtained using the technique of gas chromatography coupled to mass GC-MS. Raw data obtained were analyzed by statistical matching tests canonical, Kruskal - Wallis, cluster analysis and principal components PCA, as relevant data from the study found that higher performance and greater number of key components for the essential oil of Lemongrass correspond to samples of Coast region, to Ginger and Turmeric correspond to samples of East region. Based on all the analyses carried out in this study, it is concluded that both the climatic variables such as the soil type do influence the chemical composition of the essential oils.